Adsorption of lead(II) onto PE microplastics as a function of particle size: Influencing factors and adsorption mechanism. (October 2022) - Nguyen, Thanh-Binh; Ho, Thi-Bao-Chau; Huang, C.P.; Chen, Chiu-Wen; Chen, Wei-Hsin; Hsieh, Shuchen; Hsieh, Shu-Ling; Dong, Cheng-Di
Abstract: The adsorption of Pb ions, on high-density polyethylene (PE) microplastics (MPs) with the diameter of 48–500 μm, was examined in this study. According to the Langmuir isotherm, MP of the smallest size, 48 μm, had the greatest adsorption capacity of 0.38 μmol g −1 . The mechanism of Pb ions adsorption onto PE MPs was chemical adsorption, in particular, hydrogen bonding and surface complexation. Pb adsorption onto PE particles was proceeded at a rapid rate, as predicted by the pseudo-second-order rate model (R 2  > 0.99). The PE 48 μm had the maximum adsorption capacity of 0.44 μmol g-1 (or 0.2 mol m −2 ) at pH 5. While humic acid can operate as a bridging agent, boosting heavy metal adsorption on the surface of PE MPs, fulvic acid has the reverse effect. The findings indicated that PE particles may serve as a carrier of heavy metals in the aquatic environment, posing perceived risks to the environment and public health. Graphical abstract: Image 1 Highlights: Adsorption of lead onto PE microplastic is size-dependent. Surface charge of PE particles was controlled by the potential-determining ion, pH. Pb adsorption followed the pseudo-second-order kinetics model (R 2  > 0.99). Specific chemical adsorption played a major role on Pb adsorption. Natural organic matters have different bridging effect on lead adsorption.